Superoxide Radical Metabolism in Sweet Pepper (Capsicum annuum L.) Fruits Is Regulated by Ripening and by a NO-Enriched Environment - González-Gordo, Salvador; Rodríguez-Ruiz, Marta; Palma, José M.; Corpas, Francisco J. (Frontiers in Plant Science, 2020)
Superoxide radical (O2•-) is involved in numerous physiological and stress processes in higher plants. Fruit ripening encompasses degradative and biosynthetic pathways including reactive oxygen and nitrogen species (ROS/RNS). Using sweet pepper (Capsicum annuum L.) fruits at different ripening stages and under a nitric oxide (NO)-enriched environment, the metabolism of O2•- was evaluated at biochemical and molecular levels considering the O2•- generation by a NADPH oxidase system and its dismutation by superoxide dismutase (SOD). At biochemical level, seven O2•- generating NADPH-dependent oxidase isozymes (also called respiratory burst oxidase homologs, RBOHs; I-VII), with different electrophoretic mobility and abundance, were detected considering all ripening stages from green to red fruits and NO environment. Globally, this system was gradually increased from green to red stage with a maximum of approximately 2.4-fold increase in red fruit compared with green fruit. Significantly, breaking-point (BP) fruits with and without NO-treatment both showed intermediate values between those observed in green and red peppers, although the value in NO-treated fruits was lower compared with BP untreated fruits. The O2•- generating NADPH oxidase isozymes I and VI were the most affected. On the other hand, four SOD isozymes were identified by non-denaturing electrophoresis, one MnSOD, one FeSOD and two CuZnSODs. However, none of these SOD isozymes showed any significant change during the ripening from green to red fruits or under NO treatment. In contrast, at molecular level both RNA-sequencing and RT-qPCR analyses revealed different patterns with downregulation of four genes RBOH A, C, D and E during pepper fruit ripening. On the contrary, it was found out the upregulation of a Mn-SOD gene in the ripening transition from immature green to red ripe stages, whereas a Fe-SOD gene was downregulated. In summary, the data reveal a contradictory behavior between activity and gene expression of the enzymes involved in the metabolism of O2•- during the ripening of pepper fruit. However, it could be concluded that the prevalence and regulation of the O2•- generation system (NADPH oxidase-like) seem to be essential for an appropriate control of the pepper fruit ripening which, additionally, is modulated in the presence of an NO-enriched environment.